The impact of municipal skills development programmes on the informal trading sector: Johannesburg (2001-2006) - Radebe, Nkosinathi Witness (My University, 2008)
This research report investigates the impact of skills development programmes on the informal traders in the City of Johannesburg (COJ). The research would like to determine if skills development provided by municipality has benefited individual traders, in terms of financial performance and increased employment. The researcher will ascertain the progress between informal traders who receive training and those who did not participate in the training programme. The report would further establish if there were any impacts at all. Was the impact directly influenced by municipal training or was because of some externalities such as trader’s innovation or trader’s organisations? To what extent has training been able to reduce the skills gap in the informal business? This research is responding to the lack of previous work on the impact of training offered to informal traders. There is a strong commitment on the part of COJ to dialogue with informal traders. Informal trading is regarded as integral part of broader economy (The Star: 2006: 21). The research was conducted through in-depth interviews with informal traders operating at Metro Mall in the City Business District (CBD). The researcher conducted interviews with service providers and municipality. The hypothesis suggests that informal traders who receive training are more productive than those who did not participate. The lack of skills in the informal business prompted the COJ to deliver skills training in an attempt to improve the condition of the informal traders. (Simon McGrath 1994), referred to this scenario as “planning for what was traditionally unplanned”. The argument is that training does not make successful informal traders. The report will argue that while training is important to informal traders who arrive in Johannesburg lacking skills, training should be monitored and be accompanied by incentives for example to help those who may not have a start-up capital. The selection criteria will have to be reviewed such that most informal traders are given equal opportunity to acquire skills necessary for the development of their business. As long as these factors, remain un-addressed there are limited potential growth in the informal business. Training should be an integral process linked to various structures such that survivalist activities are replaced by sustainable entrepreneurial business. The duty of the planners as the practitioners in the built environment is to ensure that informal trading coexist with formal business without one affecting negatively on the other. They also have a duty of influencing municipal decision-makers in ensuring that informal traders training programmes reinforce the enabling environment that would allow them to benefit and improve their business undertakings. This may be accomplished by restricting competition from illegal informal traders operating outside the mall, providing incentives to informal traders after the training and organise special events that would attract more customers at the mall. This is because “planning is a profession concerned with the management and development of human beings and their settlements within urban and rural settings. It is about the organisation of human activity in a way that will help to realise their hopes and dreams for future” (www.wits.ac.za/depts/wcs/archschool.html).
Keywords: Skills development; Informal traders; Training